Fish nutrition (Nutritional physiology & Feeding) - Csengeri, Istvan (Cantho university, 1995)
The goal of the lectures is to present some basic knowledge on fish nutrition and diet development for fish culture specialists and for candidates who are going to do research in fish nutrition.